2009
DOI: 10.1021/jp804151a
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram of P3HT/PCBM Blends and Its Implication for the Stability of Morphology

Abstract: In this work, the phase diagram of poly(3-hexyl thiophene) (P3HT) and [6,6]-phenyl C61-butyric acid methyl ester (PCBM) blends is measured by means of standard and modulated temperature differential scanning calorimetry. Blends were made by solvent-casting from chlorobenzene, as blends cast from toluene or 1,2-dichlorobenzene prove to retain effects of phase segregation during casting, hindering the determination of the phase diagram. The film morphology of P3HT/PCBM blends cast from chlorobenzene results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
350
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(391 citation statements)
references
References 38 publications
36
350
4
Order By: Relevance
“…Previous DSC analysis of [60]PCBM obtained identical features in the first cooling and second heating cycles. 40 In comparison, both bis-PCBM and Ketolactam-1 seem to feature a significantly lower degree of crystallinity, below the DSC detection limit (< 10%). As an isomeric mixture, films of bis-PCBM are expected to be non-crystalline.…”
Section: Resultsmentioning
confidence: 95%
“…Previous DSC analysis of [60]PCBM obtained identical features in the first cooling and second heating cycles. 40 In comparison, both bis-PCBM and Ketolactam-1 seem to feature a significantly lower degree of crystallinity, below the DSC detection limit (< 10%). As an isomeric mixture, films of bis-PCBM are expected to be non-crystalline.…”
Section: Resultsmentioning
confidence: 95%
“…This result could be due to the combination of chemical structure and relatively low molecular weight of the materials (reported in Supporting Information Table S1), indeed it has been reported that the Tg of P3HT with low molecular weight, is situated at temperatures as low as 12ºC [52]. Despite the difficult of the DSC measurement interpretation on the pure polymer, it is necessary to consider that after blending with fullerene molecules Tg values might change dramatically [53] by effect of restructuring. Therefore, device thermal stability not only depends on the polymer properties but also on the rest of constituents as discussed in the Introduction.…”
Section: Resultsmentioning
confidence: 98%
“…50,51 This process is extremely sensitive to the solvent used, 52,53 variations in composition, 54 annealing, [55][56][57][58][59] chemical-structure variations, [60][61][62][63] purities, 64 and processing conditions, 65 to name but a few of the related parameters when dealing with what is a fundamentally unstable system. 66 The seminal work by Yang et al demonstrated the necessity of controlled mixing of the acceptor and donor in the composite. Crystalline zones transport charges away from their point of formation, which often occurs in amorphous zones where the donor and acceptor are more closely intermingled.…”
Section: Brief Overview Of Bulk-heterojunction Opvsmentioning
confidence: 99%